Numerical simulation of convection hybrid ferrofluid with magnetic dipole effect on an inclined stretching sheet - Nur Ilyana Kamis; Lim Yeou Jiann; Sharidan Shafie; Noraihan Afiqah Rawi (Alexandria Engineering Journal, 2023)
Iron oxide nanoparticles possess magnetic characteristics that enable their control and manipulation using external magnetic fields, making them suitable for a wide range of biomedical engineering applications. Consequently, this study investigates the ferrohydrodynamic interaction of hybrid magnetic nanoparticles in an ethylene glycol plus water mixture flowing over an inclined stretching sheet, taking into account the magnetic dipole effect. The governing partial differential equations are transformed into ordinary differential equations by opting the suitable similarity variables. To obtain the numerical results, an unconditionally stable implicit difference method called the Keller box method is employed. The study analyzes the effects of the inclination angle, ferrohydrodynamic interaction, ferroparticle volume fraction, and mixed convection parameter. The results indicate that an increase in the inclination angle and mixed convective parameter enhances the velocity profile and Nusselt number, whereas the ferrohydrodynamic interaction and ferroparticle volume fraction exhibit the opposite trend. Furthermore, the study reveals that under certain conditions, the presence of magnetic oxide and cobalt iron oxide suspended in an ethylene glycol plus water mixture effectively reduces the heat transfer rate.